(untitled) - Perreault, William D. (Boston, Mass., 2005)
This work offers a thorough integration of the latest marketing themes, topics and examples, to focus on management decision-making in marketing, and provide integrated coverage of special topics such as technology, ethics, international perspectives, relationship marketing and services. This book develops and presents the "Four Ps" framework when describing the components of the marketing mix (product, price, place, promotion). Features include: integrated coverage of how developments in e-commerce are impacting marketing thinking and marketing action as well as a comprehensive discussion of marketing lessons learned from both the successes and failures of companies, including the dot.coms, in the new economy; coverage of the important new perspectives that evolve from customer relationship management (CRM) strategies and tools, and how they relate to concepts such as customer equity, customer acquisition and retention costs; and updated Internet exercises that are integrated throughout the text, along with links to companies referenced in the book.
Keywords: Marketing,Tiếp thị; Management,Quản trị